Technology Adaptation as a Decision-Making Priority in Responding to the Revolution in Military Affairs for National Defense - Harsono, Cecilia F; Sutanto, Sutanto; Harefa, Faonaso (International Humanity Advance, Business & Sciences, 2025)
This research formulates decision-making strategies to address the Revolution in Military Affairs (RMA) that affects the People's Total Defense and Security System in Indonesia. The research aims to provide recommendations to stakeholders, such as the Ministry of Defense and the House of Representatives, while also enhancing the public's role in strengthening the national defense system. The methodology used is qualitative analysis with NVivo and quantitative analysis with the Analytic Hierarchy Process (AHP). The research sample involved defense technology experts, Ministry of Defense employees, military personnel, and public administration practitioners. The research results indicate that the main priority in facing RMA is the adaptation and strengthening of technology (0.299), followed by military-civil collaboration (0.253), national defense training (0.239), and RMA socialization (0.209). These findings emphasize the importance of technology integration in the defense system, policy support from stakeholders, and public participation. Recommendations include increasing public awareness, strengthening the defense budget to above 1% of GDP, and utilizing advanced technology for defense. This research provides strategic insights for decision-making in facing global challenges, emphasizing the importance of collaboration between technology, policy, and society to create an adaptive and resilient national defense system.